The Role of Work Flexibility, Social Support, and Leadership in Improving Employee Performance in the Government and Regional Autonomy Bureau of the Aceh Governor's Office - Haswita, Desi; Edi, Edi; Prasetia, Haris; Khaliluddin, Khaliluddin; Syahputra, Romi; Supriadi, Supriadi (Mahesa Research Center, 2025)
This study aims to analyze the influence of work flexibility, social support, and leadership on employee performance in the Bureau of Government and Regional Autonomy of the Aceh Governor's Office. The research sample consisted of 45 employees who were selected purposively. Data collection was carried out using a questionnaire measured through the Likert scale, and data analysis was carried out using the multiple linear regression method to determine the influence of the three independent variables on employee performance. The results of the study show that work flexibility, social support, and leadership have a positive and significant influence on employee performance. Social support was found to have the strongest influence, with a beta coefficient of 0.38, followed by leadership at 0.31 and work flexibility at 0.25. These findings are in line with the theories of job design, social support, and transformational leadership, which emphasize the importance of flexible work policies, strong social support, and participatory leadership styles in increasing productivity. In conclusion, human resource management in government agencies needs to integrate these three factors to create a conducive work environment and encourage optimal employee performance. The implications of this research are also relevant for improving bureaucratic efficiency in the public sector.